Barriers to Environmental Journalism in Pakistan : A Qualitative Study of Journalistic Practice and Media Constraints - Farsi, Salman; Imran, Huda (Journal of Professional Research in Social Sciences, 2025)
Pakistan emits a very small percentage of the total carbon emissions in the world, but it is prone to climate change, with frequent floods, droughts, and an increase in temperature. Despite these threats, the level of environmental awareness among the citizens is low, partly because of poor communication through the media. This paper examines journalistic practice of environmental communication in Pakistan, structural and institutional constraints that inhibit effective reporting. The qualitative research design was adopted in study, relied on semi-structured interviews of five senior journalists working in print, television, and news agencies. Interview thematic analysis showed that the main issues that contribute to the undermining of environmental coverage include financial limitations, political interests, poor access to technology, poor journalist-scientist connections, and the absence of editorial interest. It is necessary to conduct specific institutional changes, financing, and the establishment of partnership networks of journalists and scientific communities.